Effects of harvesting and ginning practices on Southern High Plains cotton: fiber quality. Issue 23 (December 2019) - Wanjura, John D; Armijo, Carlos B; Delhom, Christopher D; Boman, Randal K; Faulkner, William B; Holt, Gregory A; Pelletier, Mathew G
The lint yield and fiber quality of cotton produced in the Southern High Plains of the USA have improved over the last decade, renewing interest in finding harvest and ginning practices that better preserve fiber quality. Previous research showed that picker harvesting and roller ginning may better preserve fiber quality, but conventional roller ginning was too slow to be adopted as the primary ginning system used for Upland cotton. Advancements in roller ginning technology have increased the ginning rate per unit width of rotary-knife roller gins to approximately equal that of saw gins. Research has shown that improvements in nep content and fiber length characteristics afforded by conventional roller ginning compared to saw ginning are maintained by the new high-speed roller gins (HSRGs). The objective of this work was to compare the fiber quality, seed quality, ginning rate, and lint turnout of Upland cotton produced in the Southern High Plains, harvested using a picker or a stripper, and ginned using saw or HSRG systems. The findings of this work indicate that the HSRG substantially improved the length characteristics of the Upland cultivars tested regardless of harvest method. Turnout was higher for the HSRG and for picker harvested cotton. Nep content was reduced for picker harvested cotton and the HSRG. The fiber length distribution and nep content improvements from the HSRG system make this fiber more attractive to ring spinning mills that produce high-count yarns for high-value products.